Sense of Divine Involvement and Sense of Meaning in Life: Religious Tradition as a Contingency - Jung, Jong Hyun (Journal for the scientific study of religion, 2015)
This study examines the association between sense of divine involvement and sense of meaning in life. Then it proceeds to assess how this association varies by religious tradition. Using a random and national sample from the 2007 Baylor Religion Survey, this study finds that sense of divine involvement is associated with greater odds of having a sense of meaning in life. In addition, religious affiliation modifies this association. Specifically, the positive association between sense of divine involvement and the odds of having a sense of meaning in life is observed only among evangelical Protestants, mainline Protestants, and Catholics, but not among other religionists and religious nones. I discuss how the results make contributions to knowledge about the link between religious beliefs, religious tradition, and mental health.